(untitled) (Pedagogy of Higher and Secondary Education, 2010)
The article considers a circle of problems and laws of forming the graphic culture of the future teachers technologies while studying the designing of clothes and designing with the elements of the system of automatic planning. The interrelation between the level of base knowledge on plotting, designing and level of graphic culture of students is based.